"Being Wholly Muslim and Wholly American": Exploring One Islamic School's Efforts to Educate against Extremism. Issue 6 (June 2017) - Brooks, Melanie C.; Ezzani, Miriam D.
Background/Context: Current estimates show 2, 500 Islamic State (IS) jihadists are from the United States, Australia, and Western Europe. How and in what ways formal schooling influences the radicalization process and the development of extremist worldviews is yet to be fully understood. There is little research that explores how religious schooling educates against radical thought and behavior and this article reports findings from a qualitative case study of an Islamic school in the United States that counters religious extremism through the promotion and development of an American Muslim identity in its students, an ideology that advances the idea that an individual can be wholly American and wholly Muslim without any incongruity. Purpose/Objective/Research Question/Focus of the Study: The purpose of this research was to explore one American Islamic school's efforts to counter religious extremism through the promotion and development of an American Muslim identity in its students. Two research questions guided this inquiry: (a) How does one American Islamic school attempt to develop and promote anti-extremist beliefs and behaviors through their development of an American Muslim identity in its students? (b) How is this reflective of Davies' Critical Idealism XvX Model? Research Design: For this qualitative case study, data were gathered and analyzed using Lynn Davies' Critical Idealism XvX Model, which contrasts formal education that teaches anti-extremism to education that may teach extremist worldviews. Findings/Results: The findings suggested that this Islamic school's focus on American Muslim identity reflected the components and values put forth in Davies' framework that supported anti-extremist education and thereby thwarted extremist ideologies of single-truths, silencing, obedience, utopian excellence, political ignorance, and pure identities. Establishing a "good fit" for teachers, parents, and students were essential and parents with extremist or fundamentalist ideologies tended to disenroll their children. This study also suggested that Davies' Critical Idealism XvX Model may be a useful framework for exploring religious education. Conclusions/Recommendations: The school's administrators believed in the need to re-envision the American Muslim community—moderate in outlook, resonant with American values, participative with community, and supportive and welcoming of diversity. In doing so, the school delivered an anti-extremist education that promoted social integration, democratic values, and acceptance of diversity. This moderate outlook is counter to prevailing stereotypes and thus it is imperative that research continues to explore the role formal schooling plays in educating for or against extremism.